Paving the path to Dark Matter detection - Reyes Santos, Marco Antonio; Estrada, Juan (Acta Universitaria, 2015)
In order to detect Dark Matter (DM), scientists in the DAMIC (Dark Matter In CCDs) Collaboration have set an experimental array of Charge-Coupled Devices (CCDs) in a nickel mine underground, and have developed all analysis tools to discern any known trace of conventional matter from what they expect to find in case a DM particle crosses the CCDs. In order to calibrate the signals from the CCDs, they have also designed experiments to quantify neutron-silicon interactions, assuming that neutrons can mimic DM interactions in the CCDs. Here we present preliminary results from the analysis of data obtained in these experiments.
Keywords: Array; Array; Array